Splendor da ciel rediscovered music from a Florentine Trecento manuscript - Giovanni Mazzuoli 1360-1426; Mazzuoli, Piero -1430; Paolo da Firenze 1355-1436; Zachara, Antonio 1350-1430; Jacopo da Bologna; Salinis, Hubertus de; Giovanni da Cascia (Outhere, 2018)
The Chapter Archive of San Lorenzo in Florence houses a manuscript which served to record church properties. However, its parchment leaves originally belonged to a music manuscript compiled around 1410-20 in Florence. Later, the music was erased to create space for new content. Although its musical origins are known for over thirty years, its 216 compositions have been considered largely illegible. Recently, scholars and scientists from the University of Hamburg were able to render it visible again, using the technology of multispectral imaging. The San Lorenzo Palimpsest, as the collection is known today, is an invaluable source of secular polyphonic music composed between the fourteenth and the beginning of the fifteenth centuries. The anthology not only includes new readings for compositions known from other contemporary manuscripts, but contains completely unknown works by Florentine composers. La Morra breathes new life into these rediscovered musical treasures, most of which are recorded here for the first time
Consists of previously unreleased material from San Lorenzo Palimpsest, Florence, Archivio del Capitolo di San Lorenzo
Complete performer credits and program (in English with translations in German and French) in booklet (42 pages : illustrations) laid in container
Keywords: CD